The OEIS is supported by the many generous donors to the OEIS Foundation.

 Year-end appeal: Please make a donation to the OEIS Foundation to support ongoing development and maintenance of the OEIS. We are now in our 59th year, we have over 358,000 sequences, and we’ve crossed 10,300 citations (which often say “discovered thanks to the OEIS”). Other ways to Give
 Hints (Greetings from The On-Line Encyclopedia of Integer Sequences!)
 A101220 a(n) = Sum_{k=0..n} Fibonacci(n-k)*n^k. 45
 0, 1, 3, 14, 91, 820, 9650, 140601, 2440317, 49109632, 1123595495, 28792920872, 816742025772, 25402428294801, 859492240650847, 31427791175659690, 1234928473553777403, 51893300561135516404, 2322083099525697299278 (list; graph; refs; listen; history; text; internal format)
 OFFSET 0,3 COMMENTS In what follows a(i,j,k) denotes a three-dimensional array, the terms a(n) are defined as a(n,n,n) in that array. - Joerg Arndt, Jan 03 2021 Previous name was: Three-dimensional array: a(i,j,k) = expansion of (x(1+i*x-j*x))/((-1+j*x)(-1+x+x^2)), read by a(n,n,n). a(i,j,k) = the k-th value of the convolution of the Fibonacci numbers [A000045] with the powers of i = Sum[a(i-1,j,m], {m=0...k}], both for i = j and i > 0; a(i,j,k) = a(i-1,j,k) + a(j,j,k-1), for i,k > 0; a(i,1,k) = Sum[a(i-1,0,m), {m=0...k}], for i > 0. a(1,1,k) = Fib(k+2) - 1; a(2,1,k) = Fib(k+3) - 2; a(3,1,k) = Luc(k+2) - 3; a(4,1,k) = 4Fib(k+1) + Fib(k) - 4; a(1,2,k) = 2^k - Fib(k+1); a(2,2,k) = 2^(k+1) - Fib(k+3); a(3,2,k) = 3(2^k - Fib(k+2)) + Fib(k); a(4,2,k) = 2^(k+2) - Fib(k+4) - Fib(k+2); a(1,3,k) = (3^k + Luc(k-1)) / 5, for k > 0; a(2,3,k) = (6(3^(k-1)) - Luc(k)) / 5, for k > 0; a(3,3,k) = (3^(k+1) - Luc(k+2)) / 5; a(4,3,k) = (4(3^k) - Luc(k+2) - Luc(k+1)) / 5...all for which Fib(k) denotes the k-th Fibonacci number and Luc(k) denotes the k-th Lucas number [A000032]. LINKS Eric Weisstein's World of Mathematics, Fibonacci Number Eric Weisstein's World of Mathematics, Lucas Number FORMULA a(i, j, 0) = 0, a(i, j, 1) = 1, a(i, j, 2) = i+1; a(i, j, k) = ((j+1)*a(i, j, k-1)) - ((j-1)*a(i, j, k-2)) - (j*a(i, j, k-3)), for k > 2. a(i, j, k) = Fib(k) + i*a(j, j, k-1), for i, k > 0, where Fib(k) denotes the k-th Fibonacci number. a(i, j, k) = (Phi^k - (-Phi)^-k + i(((j^k - Phi^k) / (j - Phi)) - ((j^k - (-Phi)^-k) / (j - (-Phi)^-1)))) / sqrt(5), where Phi denotes the golden mean/ratio [A001622]. i^k = a(i-1, i, k) + a(i-2, i, k+1). A104161(k) = Sum[a(k-m, 0, m), {m=0...k}]. a(i, j, 0) = 0, a(i, j, 1) = 1, a(i, j, 2) = i+1, a(i, j, 3) = i(j+1) + 2; a(i, j, k) = ((j+2)a(i, j, k-1)) - ((2j)a(i, j, k-2)) - a(i, j, k-3) + (ja(i, j, k-4)), for k > 3. a(i, j, 0) = 0, a(i, j, 1) = 1; a(i, j, k) = a(i, j, k-1) + a(i, j, k-2) + (ij^(k-2)), for k > 1. G.f.: (x*(1+i*x-j*x)) / ((-1+j*x)(-1+x+x^2)). a(n, n, n) = Sum[Fibonacci(n-k)n^k, {k, 0, n}]. - Ross La Haye, Jan 14 2006 Sum[C(k,m)(i-1)^m,{m,0,k}] = a(i-1,i,k) + a(i-2,i,k+1), for i > 1. - Ross La Haye, May 29 2006 a(3, 3, k+1) - a(3, 3, k) = A106517(k). a(1, 1, k) = A001924(k) - A001924(k-1), for k > 0; a(2, 1, k) = A001891(k) - A001891(k-1), for k > 0; a(3, 1, k) = A023537(k) - A023537(k-1), for k > 0; Sum[a(i-j+1, 0, j), {j, 0, i+1}] - Sum[a(i-j, 0, j), {j, 0, i}] = A001595(i). - Ross La Haye, Jun 03 2006 a(i,j,k) = a(j,j,k) + (i-j)a(j,j,k-1), for k > 0. a(n) ~ n^(n-1). - Vaclav Kotesovec, Jan 03 2021 EXAMPLE a(1,3,3) = 6 because a(1,3,0) = 0, a(1,3,1) = 1, a(1,3,2) = 2 and 4*2 - 2*1 - 3*0 = 6. MATHEMATICA Join[{0}, Table[Sum[Fibonacci[n-k]*n^k, {k, 0, n}], {n, 1, 20}]] (* Vaclav Kotesovec, Jan 03 2021 *) PROG (PARI) a(n)=sum(k=0, n, fibonacci(n-k)*n^k). - Joerg Arndt, Jan 03 2021 CROSSREFS a(0, j, k) = A000045(k); a(1, 0, k) = A000045(k+1), for k > 0; a(1, 1, k) = A000071(k+2); a(1, 2, k) = A027934(k-1), for k > 0; a(1, 3, k) = A098703(k); a(2, 0, k) = A000032(k), for k > 0; a(2, 1, k) = A001911(k); a(2, 2, k) = A008466(k+1); a(3, 0, k) = A000285(k-1), for k > 0; a(3, 1, k) = A027961(k); a(3, 3, k) = A094688(k); a(4, 0, k) = A022095(k-1), for k > 0; a(4, 1, k) = A053311(k-1), for k > 0; a(4, 2, k) = A027974(k-1), for k > 0; a(5, 0, k) = A022096(k-1), for k > 0; a(6, 0, k) = A022097(k-1), for k > 0; a(i, 0, i) = A094588(i). a(2, 3, k) = A106517(k-1), for k > 0; a(1, 2, k+1) - a(1, 2, k) = A099036(k); a(3, 2, k+1) - a(3, 2, k) = A104004(k); a(4, 2, k+1) - a(4, 2, k) = A027973(k); a(1, 3, k+1) - a(1, 3, k) = A099159(k). a(i, 0, i+1) = A007502(i+1); a(i, 0, i+2) = A088209(i). a(i, 0, k) = A109754(i, k). a(14, 0, k) = A022105(k-1), for k > 0. a(7, 0, k) = A022098(k-1), for k > 0; a(8, 0, k) = A022099(k-1), for k > 0; a(9, 0, k) = A022100(k-1), for k > 0; a(10, 0, k) = A022101(k-1), for k > 0; a(11, 0, k) = A022102(k-1), for k > 0; a(12, 0, k) = A022103(k-1), for k > 0; a(13, 0, k) = A022104(k-1), for k > 0; a(15, 0, k) = A022106(k-1), for k > 0; a(16, 0, k) = A022107(k-1), for k > 0; a(17, 0, k) = A022108(k-1), for k > 0; a(18, 0, k) = A022109(k-1), for k > 0; a(19, 0, k) = A022110(k-1), for k > 0. a(i, i+1, 3) = A002522(i+1); a(i, i+1, 4) = A071568(i+1). a(2^i-2, 0, k+1) = A118654(i, k), for i > 0. Sequence in context: A125788 A183611 A259903 * A078456 A195134 A089462 Adjacent sequences: A101217 A101218 A101219 * A101221 A101222 A101223 KEYWORD nonn,easy AUTHOR Ross La Haye, Dec 14 2004 EXTENSIONS New name from Joerg Arndt, Jan 03 2021 STATUS approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recents
The OEIS Community | Maintained by The OEIS Foundation Inc.

Last modified December 10 02:09 EST 2022. Contains 358712 sequences. (Running on oeis4.)